The Post-Bandung Order and the Multiplex Trap: Reconsidering Indonesian Agency and the Imagination of the Global South - Utama, Virdika Rizky; Mukhtar Abdullah (Kementerian Luar Negeri Republik Indonesia, 2025)
The 1955 Bandung Asian-African Conference is often regarded as a historic moment that paved the way for envisioning a more equitable global order. However, after seven decades, the spirit of Bandung has been preserved more as a ceremonial symbol than actualised into a substantive agenda. Utilising Amitav Acharya's framework of the multiplex world, this article proposes the concept of the